Impact of Meteorological Conditions and Human Activities on Air Quality During the COVID-19 Lockdown in Northeast China - Wang, Taihao; Du, Huadong; Zhao, Zezheng; Zhang, Jiping; Zhou, Chengjun (Frontiers in Environmental Science, 2022)
During the lockdown implemented to curb the spread of COVID-19, human activities have drastically reduced, providing a valuable opportunity to study and compare the impact of meteorological conditions and human activities on air quality. In this study, large-scale weather circulation, local meteorological conditions, and the impact of human activities are comprehensively considered, and changes in the concentration of major air pollutants in the northeast during this period are systematically studied. The large-scale weather circulation patterns that mainly affect the northeast region are divided into nine types by using the T-mode PCA (Principal components analysis) objective circulation classification method. It is found that the northeast region is located at the edge of weak high pressure (Types 1, 2, and 7) and at the rear of high pressure (Type 4) and has higher concentrations of PM2.5, NO2, SO2, and CO; in cyclonic weather systems, low vortices (Types 3 and 5) and under the influence of the updraft (Type 6) in front of the trough, the ozone concentration is higher. The changes in the concentrations of PM2.5, NO2, CO, SO2, and O3 in the three cities, namely Shenyang, Changchun, and Harbin, during the lockdown period are compared, and it is found that the concentrations of PM2.5, NO2, CO, and SO2 have a tendency to first decrease and then increase, while the changes of O3 concentration are cyclical and increased significantly during this period. This demonstrates that pollutants such as PM2.5, NO2, CO, and SO2 are more susceptible to human activities and local meteorological conditions, and changes in O3 concentration are more closely related to changes in weather circulation types. Finally, the FLEXPART-WRF model is used to simulate the pollution process of nine circulation types, which confirms that particulate pollution in the northeast is mainly affected by local emissions and local westward sinking airflow.